REVISTA DIGITAL - Ciencias Penales, Maestría en (2011)
Director de la RevistaDr. Javier Llobet Rodríguez (Director del Posgrado en Derecho de la Universidad de Costa Rica) Miembros del Consejo editorialDr. Javier Llobet Rodríguez. Director de la Revista (Profesor de la Universidad de Costa Rica) Dr. Carlos Tiffer Sotomayor (Profesor de la Universidad de Costa Rica) Dr. Alvaro Burgos (Profesor de la Universidad de Costa Rica) Dr. Alfredo Chirino Sánchez (Profesor de la Universidad de Costa Rica) Dr. Gustavo Chan Mora (Profesor de la Universidad de Costa Rica) Consejo Consultivo InternacionalProf. Msc. Alberto Bovino (Profesor de la Universidad de Buenos Aires) Prof. Dr. Edgardo Rotman (Profesor de la Universidad de Miami) Prof. Dr. Emiliano Borja (Profesor de la Universidad de Valencia, España)Prof. Dr. Braulio Espinoza (Profesor de la Universidad Autónoma de Nicaragua-León)Prof. Msc. Carlos Sánchez Escobar (Profesor de la Universidad Centroamericana José Simeón Cañas y de la Universidad Salvadoreña Alberto Masferrer) Prof. Dr. Frieder Dünkel (Profesor de la Universidad de Greifswald, Alemania) Prof. Dr. Andrés Herrera Rodríguez (Profesor de la Universidad Autónoma de Nicaragua-León) Prof. Msc. Miguel Cillero Bruñol (Profesor de la Universidad Diego Portales, Chile) Prof. Dr. Carlos Elbert (Profesor de la Universidad de Buenos Aires) Prof. Dr. José Manuel Ríos Corbacho (Profesor de la Universidad de Cádiz, España) Prof. Dr. Jaime Couso Salas (Profesor de la Universidad Diego Portales, Chile) Prof. Dr. Fernando Velásquez Velásquez (Profesor de la Universidad Sergio Arboleda, Colombia) Prof. Dr. Kai Ambos, Universidad de Göttingen (Alemania) Prof. Dr. Juan Carlos Ferré Olivé (Universidad de Huelva) Prof. Dra. Teresa Aguado Correa (Profesora de la Universidad de Sevilla)